Effect of Feeding Ddgs on Body Weight Gain, Steroid Hormones Profile, Age at Puberty and its Economics in Crossbred Heifers - Dhami, AJ; Shah, SV; Chaudhari, DV; Lunagaria, PM; Chaudhary, MM; Sarvaiya, NP (The Indian Journal of Animal Reproduction, 2021)
The study was undertaken on HF x Kanrej heifers (n=24) from average 8 months till 19 months of age. The aim was to evaluate the effect of feeding distillers dried grains with soluble (DDGS) and Soy DOC alone or in combination with cereal and/ or leguminous straws as TMR on their body weight gain, serum steroid hormones profile, ovarian changes, age at puberty/sexual maturity and its economic benefits. Monthly gain in body weight, and serum P4 and E2 levels increased progressively with advancing age. Ovarian activity in terms of follicles and corpus luteal (CL) was noticed from 14 months of age onwards with pregnancy in more than 60% heifers by 19 months and 100% by 23 months of age. Higher body weight gain (BWG) was observed in DDGS and legume straw fed groups as compared to soy DOC and cereal straw fed groups. Average age at onset of puberty and sexual maturity/conception were 552.21±10.72 and 616.79±15.67 days, respectively, with mean number of AIs per conception as 2.83±0.40. Overall, supplementation of DDGS and legume gotar in ration did not influence the reproductive hormone parameters and age at maturity. Though daily feed cost (`/head) remained the same, the feed costs per kg BW gain (`) were reduced significantly (P<0.01) in heifers fed half and full soy DOC replacement with DDGS (135.83±2.42, and 122.42±2.34 vs 148.00±2.96). So it can be concluded that feeding TMR consisting of DDGS in place of soy DOC in concentrate mixture and a mixture of legume straw and cereal straw (groundnut gotar and wheat straw) to growing crossbred heifers is superior with respect to body weight gain, steroid hormone profile and improved reproductive efficiency.